The Correlation Between Emotional Intelligence and The Students’ English Academic Achievement - Rizka Indahyanti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
This research aimed at describing the correlation between emotional intelligence and Students’ English academic achievement. This research used correlational design. The population was the second year students of SMA Negeri 1 Parepare and the method used for taking sample was simple random sampling. The data were obtained through questionnaires and document study. The data on students’ emotional intelligence and English academic achievement were analyzed by using inferential and descriptive statistics, Pearson Product Moment correlation analysis through SPSS 27 for windows to find out whether or not there was correlation between them. The result of the research showed that there was a positive correlation between students’ emotional intelligence and English academic achievement (r = 0.892)  It was concluded that the correlation between emotional intelligence English academic achievement of the second year students of SMA Negeri 1 Parepare were very high. The positive coefficient indicated the positive correlation, that if the emotional intelligence increases, English academic achievement will also increase.